Queere Vielfalt im Fußball Perspektiven aus Forschung und Praxis - Hirschfeld, Magnus (Verlag Barbara Budrich, 2023)
Soccer (football) could become an arena that showcases queer diversity and reflects the progress that society has made in accepting and embracing LGBTIQ* communities worldwide. The sport's wide-reaching popular significance, its ability to unify, and its highly publicized nature predestines soccer for being an outlet that continues to increase the visibility of LGBTIQ*-identifying athletes. This anthology strives to contribute to an ongoing exchange on conditions for more sexual and gender diversity. The scientific contributions discuss steps towards their sustainable realization from a variety of scholarly and empirical perspectives.